2021
DOI: 10.1055/s-0040-1722717
|View full text |Cite
|
Sign up to set email alerts
|

Do All Notochordal Lesions Require Proton Beam Radiotherapy? A Proposed Reclassification of Ecchordosis Physaliphora as Benign Notochord Cell Tumor

Abstract: Objectives Ecchordosis physaliphora (EP) is a benign notochord lesion of the clivus arising from the same cell line as chordoma, its malignant counterpart. Although usually asymptomatic, it can cause spontaneous cerebrospinal fluid (CSF) rhinorrhea. Benign notochordal cell tumor (BNCT) is considered another indolent, benign variant of chordoma. Although aggressive forms of chordoma require maximal safe resection followed by proton beam radiotherapy, BNCT and EP can be managed with close imaging surveillance wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…These presentations are similar to those of the patients in the largest case series to date in which 2 asymptomatic patients were diagnosed, one after undergoing imaging for a meningioma and the other undergoing imaging for nighttime tinnitus. 21 Interestingly, a recent systematic review by Gupta et al 14 gathered 60 cases of BNCTs that were diagnosed during investigation for a broad spectrum of symptoms. Headache and CSF rhinorrhea were the most common presentations followed by abducens nerve palsy, but in many of the cases, the presenting symptom was nonspecific such as dizziness, tinnitus, hearing loss, and confusion, thus lacking clear correlation to any clival lesion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These presentations are similar to those of the patients in the largest case series to date in which 2 asymptomatic patients were diagnosed, one after undergoing imaging for a meningioma and the other undergoing imaging for nighttime tinnitus. 21 Interestingly, a recent systematic review by Gupta et al 14 gathered 60 cases of BNCTs that were diagnosed during investigation for a broad spectrum of symptoms. Headache and CSF rhinorrhea were the most common presentations followed by abducens nerve palsy, but in many of the cases, the presenting symptom was nonspecific such as dizziness, tinnitus, hearing loss, and confusion, thus lacking clear correlation to any clival lesion.…”
Section: Discussionmentioning
confidence: 99%
“…14 In their cohort Sooltangos et al reported that 5 of 7 patients presented with CSF rhinorrhea and either a clival defect on CT or sequelae of a defect such as pneumocephalus. 21 Veiceschi et al reported that 4 of their 5 patients presented with a CSF leak and 1 with meningitis; however, none were found to have bony defects on imaging. 22 In our cohort, patients who were found to have bone erosion did not have CSF leakage or pneumocephalus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation